Association between trait mindfulness and self-efficacy in sports-disadvantaged college students in China: the chain mediating role of exercise motivation and persistence - Xu, Kuo; Zhu, Lin; Li, Yun; Cao, Yang; Zhang, Guodong (Frontiers in Psychology, 2025)
ObjectiveThis study investigates the effect of trait mindfulness on self-efficacy in sports-disadvantaged Chinese college students, focusing on the sequential mediating roles of exercise motivation and persistence, to inform interventions that enhance physical activity and psychological well-being.MethodA randomly selected sample of 600 sports-disadvantaged college students in China was surveyed, yielding 588 valid responses (male = 296, 50.3%; female = 292, 49.7%). Participants ranged in age from 18 to 23 years (M = 20.06, SD = 1.44). Among them, 45.1% reported smoking and 58.8% reported drinking. The assessment instruments included the Trait Mindfulness Scale, the Exercise Motivation Scale, the Self-Efficacy Scale, and the Exercise Persistence Scale. Data were analyzed using SPSS 26.0 and the PROCESS macro (version 4.1).ResultsSignificant correlations were identified among trait mindfulness, self-efficacy (r = 0.581, p < 0.01), exercise motivation (r = 0.585, p < 0.01), and exercise persistence (r = 0.545, p < 0.01) within the group of sports-disadvantaged college students. Exercise motivation was significant correlated with both exercise persistence (r = 0.592, p < 0.01) and self-efficacy (r = 0.679, p < 0.01). Exercise persistence also showed a significant correlation with self-efficacy (r = 0.639, p < 0.01). In the effect of trait mindfulness on self-efficacy among sports-disadvantaged college students, both exercise motivation (β = 0.224, 95% confidence interval (CI): [0.176, 0.277]) and exercise persistence (β = 0.100, 95% CI [0.067, 0.136]) demonstrated significant mediating effects. Furthermore, exercise motivation and exercise persistence exhibited a significant chain mediating effect in the influence of trait mindfulness on self-efficacy (β = 0.072, 95% CI [0.050, 0.099]).ConclusionThis study offers critical theoretical insights into the interplay between trait mindfulness, exercise behavior, and self-efficacy among sports-disadvantaged college students. It provides a foundation for developing targeted interventions and practical guidance for universities in enhancing sports education, optimizing resource allocation, and establishing psychological support systems. By addressing the unique needs of this population, institutions can foster greater physical engagement and psychological well-being, thereby advancing overall student health.